Portfolio for the Planet. - Newmark, Tammy (Taylor & Francis, 2011)
Rapid growth of the global economy has accelerated the degradation of the Earth's most important asset: the environment. Increasing poverty and challenges arising from climate change further threaten the planet's natural systems. With a rising global population, the demand on natural resources to cover even basic human needs is intensifying -- supporting businesses that promote the sustainable use of natural resources and help ensure their long-term viability is imperative. As part of a pioneering movement to harness business towards effecting environmental change, The Nature Conservancy launc.